The Relationship between Chlorophyll a and Total Phosphorus (Total-P) in Perupuk Lake, Perhentian Raja Sub-District, Kampar, Riau - Andika Ramadhani; Asmika H. Simarmata; Budijono Budijono (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
The province of Riau has many freshwater bodies that play a very important role in the lives of the surrounding communities. This study aims to determine the relationship between chlorophyll a and Total-P (Total Phosphorus) concentrations, and to evaluate the trophic status of Lake Perupuk in Perhentian Raja District, Kampar Regency, Riau Province. This study was conducted from October to December 2024 at three stations: Station 1 (estuary, without settlements), Station 2 (main lake area with fish cages), and Station 3 (estuary with settlements and agricultural activities). Sampling was carried out five times at one-week intervals at the surface and at a depth of 2 Secchi. The parameters measured included chlorophyll a, Total-P, temperature, transparency (Secchi depth), pH, dissolved oxygen (DO), free carbon dioxide (CO2), and nitrate. The results showed that chlorophyll a concentration ranged from 11.04 to 14.14 µg/L, with the highest value at Station 2 (14.14 µg/L) and the lowest at Station 1 (11.04 µg/L). Total-P concentrations ranged from 0.0168 to 0.0338 mg/L, following the same pattern: highest at Station 3 (0.0338 mg/L) and lowest at Station 1 (0.0168 mg/L). Simple regression analysis showed an insignificant relationship between Total-P and chlorophyll-a (R² = 0.0266–0.0774), indicating that, in mesotrophic waters, other factors, such as light and nitrogen availability, also affect chlorophyll-a concentrations. Based on chlorophyll a and Total-P concentrations, Lake Perupuk is categorized as a mesotrophic water body, with supporting parameters within the optimal range for aquatic organisms